Space-vector hysteresis modulation for neutral-diode-clamped inverter in active power filter applications - Fereidouni, Alireza; Masoum, Mohammad Sherkat (Journal of Electrical Engineering, 2015)
A space-vector hysteresis modulation (SVHM) technique is presented in this paper for three-level neutral-point-clamped (TLNPC) multilevel inverter for active power filter (APF) applications. The main responsibility of this modulation technique is to force the actual current to reach the reference current and, simultaneously, balance the capacitor voltages. This scheme is implemented in the stationary reference frame (SRF) to avoid interphase dependency in three-phase floated neutral point (TP-FNP) systems. The spacevector-based method permits for the efficient application of zerovoltage vectors and avoids high switching frequencies triggered by phase interaction in TPFNP systems. The approach comprises of performing two alternative hysteresis strategies around the error vector in SRF. Then, based on the present location of it, the next voltage vector is selected to minimize the next error vector and also balance the capacitor voltages. The performance of the proposed technique is investigated and verified through detailed simulation studies for both steady-state and transient conditions.